Perlindungan Hukum terhadap Korban Bullying dalam Perspektif Hak Asasi Anak di Dunia Pendidikan - Jamaluddin Jamaluddin; Muh. Amin (Lembaga Yasin AlSys, 2025)
The issue of child protection from acts of violence—particularly bullying—has been widely studied; however, research specifically addressing legal protection for bullying victims from the perspective of children's rights in the educational context remains limited. This study aims to analyze the legal protection afforded to victims of bullying within the framework of children's human rights, using case studies from several schools in South Sulawesi. A normative juridical approach was employed, supported by empirical data collected through legal document analysis and case reviews. The data were analyzed qualitatively and descriptively. The findings reveal that legal protection for bullying victims is predominantly reactive, with most responses occurring only after violations have taken place. Preventive measures—such as education on children's rights and institutionalized anti-bullying policies—are yet to be effectively implemented. Coordination among schools, parents, and child protection agencies remains weak, often resulting in informal, family-based resolutions that fail to guarantee the restoration of victims’ rights. These findings reinforce the dual framework of preventive and repressive legal protection as conceptualized by Philipus M. Hadjon (1987) and underscore the urgent need for the establishment of school-level institutional mechanisms integrated with regional child protection bodies. The study concludes that child protection systems within educational settings require a comprehensive, rights-based approach supported by multi-stakeholder collaboration. The practical implications are directed at local governments and educational institutions in developing equitable and sustainable child protection frameworks. This research also opens avenues for further policy exploration in other regions as part of strengthening the national child protection system.